FORMULASI DAN UJI ANTIDIARE SEDIAAN PATCH TRANSDERMAL EKSTRAK DAUN SENGGANI (Melastoma malabathricum L.) TERHADAP KELINCI - Winata, Hanafis Sastra; Abadi, Hafizhatul; Leny, Leny; Andry, Muhammad; Ngete, Ani Florida; Yudianto, Tri; Nurjanah, Ayu; Pamungkas, Barolym Tri; Gumilar, Roni (AGRIBIOS, 2024)
One plant that has been used for traditional medicine with good results is Melastoma (Melastoma malabatricum L.). The plant known as Melastoma has three active compounds: tannins, saponins, and flavonoids. Melastoma leaves work well to cure diarrhoea. Adhesive patches with medication applied topically are called transdermal patches. Melastoma leaf extract transdermal patch formulations were utilised in this study, which employed laboratory experimental techniques. The potential of Melastoma leaf extract transdermal patch preparation formula as an antidiarrheal for rabbits was the subject of the study. Concentrations of extract: 10%, 20%, and 30%. Organoleptic testing, pH tests, weight uniformity tests, moisture tests, thickness tests, and fold resistance tests were the preparatory assessment parameters that were conducted. The characteristics of the antidiarrheal test were timing of diarrhoea occurrences, consistency of the stool, frequency of diarrhoea, and length of diarrhoea, all of which were monitored for six hours. The evaluation of the Melastoma leaf extract transdermal patch formulation demonstrated a significant difference, namely <0.05, according to the results of the ANOVA data analysis. The antidiarrheal test parameters had a significant difference between each concentration, namely <0.05, according to the findings of the ANOVA data analysis. The conclusions was possible to use a transdermal patch formulation of Melastoma leaf extract (Melastoma malabathricum L.) at a 30% concentration to prevent diarrhoea by making stools softer.